A Novel Mixed Reality Solution Based on Learning Environment for Sutures in Minor Surgery - Ana Rojo; Laura Raya; Alberto Sanchez (Applied Sciences, 2021)
Minor Surgery Sutures is a fundamental skill for healthcare professionals. However, in the educational field, the practice of suturing is sometimes limited and reduced, with more theoretical than practical study. In order to facilitate learning, our goal is to develop an immersive and interactive educational tool that complements theoretical study, called Suture MR. This application could enhance suture procedural skills in the fields of nursing and medicine. Applying Mixed Reality techniques, we generate a 3D model of an arm with a full-scale wound. Realistically, the user will simulate the suture movements as part of the learning process. The application has surgical clamps and a needle holder that are virtually visualized in the user’s hands, allowing gestures and movements faithful to the real ones. In this article, we want to demonstrate the usability of our environment and the feasibility of using Mixed Reality learning experiences in clinical practical training as a complement to theoretical training. The results of the study reveal a greater perception of learning and the willingness of students to use this methodology.